2007
DOI: 10.1111/j.1468-1331.2006.01593.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid tau, phospho‐tau181 and β‐amyloid1−42 in idiopathic normal pressure hydrocephalus: a discrimination from Alzheimer's disease

Abstract: The aim of the present study was the quantitation of total tau protein (tau(T)), tau phosphorylated at threonine 181 (tau(P-181)) and beta-amyloid(1-42) (Abeta42) in the cerebrospinal fluid (CSF) of patients with idiopathic normal pressure hydrocephalus (iNPH), Alzheimer's disease (AD) and controls. Double sandwich ELISAs (Innogenetics) were used for the measurements. Total tau was significantly increased in iNPH and highly increased in AD as compared with the control group, whilst Abeta42 was decreased in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(81 citation statements)
references
References 31 publications
7
67
0
6
Order By: Relevance
“…CSF biomarkers p-tau, Aβ 1-38 /Aβ 1-42 ratio, and Aβ 1-42 /p-tau ratio [10,13] were prognostic predictors of cognitive function (Table 3). Moreover, analysis of the Aβ 1-38 /Aβ 1-42 ratio revealed that, while the "Improved Cognitive group" showed a tendency to shift from Aβ 1-42 to Aβ 1-38 2 years after surgery, the "Poor Cognitive group" showed similar results before and 2 years after the same.…”
Section: Discussionmentioning
confidence: 99%
“…CSF biomarkers p-tau, Aβ 1-38 /Aβ 1-42 ratio, and Aβ 1-42 /p-tau ratio [10,13] were prognostic predictors of cognitive function (Table 3). Moreover, analysis of the Aβ 1-38 /Aβ 1-42 ratio revealed that, while the "Improved Cognitive group" showed a tendency to shift from Aβ 1-42 to Aβ 1-38 2 years after surgery, the "Poor Cognitive group" showed similar results before and 2 years after the same.…”
Section: Discussionmentioning
confidence: 99%
“…19,30 Data are accumulating that the main use of ptau could be in differentiat ing aD from other forms of dementia. [31][32][33] Assay development for core biomarkers the discovery that aβ is produced during normal cell metabolism and secreted into the CsF was the basis for developing an aβ biomarker for aD. 34 the subsequent finding that aβ 1-42 is the most abundant species of aβ in amyloid plaques led to the development of assays for this aβ isoform.…”
Section: Core Biomarkersmentioning
confidence: 99%
“…Certaines d'entre elles montraient des taux diminués d'A␤-42 (comme dans la MA) ainsi qu'une tendance à une baisse des taux de P-tau dans l'HPNi par rapport à des sujets sains [38]. Kapaki et al [39] ont établi qu'un taux de P-tau supérieur à 47 pg/mL permettait de distinguer une MA d'une HPNi. Kang et al [38] ont noté un ratio P-tau/A␤-42 significativement plus élevé chez des patients HPNi non-répondeurs à la PL déplétive.…”
Section: Le Dosage Des Biomarqueurs Dans Le Lcrunclassified